ANALYSIS OF IMPLEMENTATION OF MUDHARABAH DEPOSITS BASED ON STATEMENT OF FINANCIAL ACCOUNTING STANDARDS 105 AT BSI CITARUM BANDUNG BRANCH - Dudang Gojali; Iwan Setiawan; Ramadhani Irma Tripalupi; Hana Aulia Islamiati (FEBI UIN Sunan Gunung Djati Bandung, 2022)
Mudharabah deposits are a type of fund investment product that uses a mudharabah contract. Mudharabah is a cooperation agreement to seek profit between capital and work/business. The agreement occurs between the depositor (investment account) or investment account holder and the Islamic bank itself as mudharib. The first party acts as the owner of the funds (shahibul maal) and the second party acts as the fund manager (mudharib) with profits divided according to the agreement of both parties. The purpose of this study was to determine, analyze and evaluate the mechanism, procedure for implementing mudharabah deposits at Bank Syariah Indonesia Bandung Citarum Branch Office and conformity with Statement of Financial Accounting Standards 105 regarding mudharabah accounting transactions. The study used a descriptive method with a qualitative approach. The results showed that the mudharabah deposit mechanism at Bank Syariah Indonesia Bandung Branch Office was in accordance with the pillars and conditions contained in the mudharabah contract. The accounting treatment for mudharabah deposits is in accordance with Statement of Financial Accounting Standards 105.